2011
DOI: 10.1021/bi201637p
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Specific Structural Changes in the Vitamin D Receptor in Solution

Abstract: Vitamin D receptor (VDR) is a member of the nuclear hormone receptor superfamily. When bound to a variety of vitamin D analogs, VDR manifests a wide diversity of physiological actions. The molecular mechanism by which different vitamin D analogs cause specific responses is not understood. The published crystallographic structures of the ligand binding domain of VDR (VDR-LBD) complexed with ligands that have differential biological activities have exhibited identical protein conformations. Here we report that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 34 publications
(71 reference statements)
3
48
0
Order By: Relevance
“…These results suggest that basal species may lack the ability to form transcriptionally active conformations with LCA. This is likely due to an inability of LCA to re-localize helices H2, H3, H11 and H12 which induces a structural transition that triggers a mousetrap-like mechanism and stabilizes ligand binding and co-regulator recruitment [45]. Future studies to determine the crystal structures of basal VDRs or zebrafish VDRβ complexed with LCA may be very informative with regards to revealing species-specific differences in VDR conformations associated the observed functional differences.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that basal species may lack the ability to form transcriptionally active conformations with LCA. This is likely due to an inability of LCA to re-localize helices H2, H3, H11 and H12 which induces a structural transition that triggers a mousetrap-like mechanism and stabilizes ligand binding and co-regulator recruitment [45]. Future studies to determine the crystal structures of basal VDRs or zebrafish VDRβ complexed with LCA may be very informative with regards to revealing species-specific differences in VDR conformations associated the observed functional differences.…”
Section: Discussionmentioning
confidence: 99%
“…Screening of synthetic ligands of the vitamin D receptor and other mammalian NHRs has demonstrated that even small changes in ligand structures can strongly affect gene transcription (Brown and Slatopolsky, 2008; Singarapu et al, 2011; Wollam and Antebi, 2011). Yet there are few approaches to comprehensively identify the endogenous NHR ligands from complex animal metabolomes, whose chemical annotations remain largely incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Precise knowledge of ligand structures and biosynthetic pathways is essential for understanding NHR function (Mangelsdorf et al, 1995; Wollam and Antebi, 2011), because even small differences in ligand structures may result in dramatic changes of transcriptional activity and specificity (Brown and Slatopolsky, 2008; Singarapu et al, 2011). However, the endogenous ligands of many NHRs remain poorly characterized, in part because ligands constitute very minor components of highly complex animal metabolomes (Schupp and Lazar, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A 4-fold molar excess of the 13-residue peptide from DRIP205, which contains the LxxLL motif mimicking the co-activator was added to the final NMR sample [43] prior to data collection. To better estimate level of perdeuteration, TROSY (transverse relaxation-optimized spectroscopy) based 15 N resolved 3D- 1 H, 1 H NOESY spectra were collected.…”
Section: Methodsmentioning
confidence: 99%